Comparison of Thermodynamics and Kinetics of Malachite Green Adsorption onto Chitin and Chitosan - Sriuttha, Manop; Wittayanarakul, Kitiyaporn (Asian Journal of Chemistry, 2015)
The adsorption of Malachite green by chitin and chitosan is investigated and compared by the adsorption method. The results shows that the Langmuir isotherm can well described the Malachite green adsorption for the chitin and chitosan. The maximum quantities of the Malachite green adsorption by the chitin and chitosan are 97.09 and 166.67 mg/g, respectively, indicating that the chitosan has more effective than the chitin two times approximately. The thermodynamic data also suggests that the chitosan is more favourable than the chitin.